Organizational Commitment in Nursing - Handan Eren; Meltem Demirgöz Bal (Association of Nurse Managers, 2015)
Organizational commitment, as a result of the organization-employee relationship, is the employees feel about the organization that runs the power. Organizations to ensure that they are satisfied with the organization work of employees, goods and / or services is as important as producing. The majority of the health care provider in the form of nurses, for the success of the organization increase their commitment to the organization of nurses is a necessity. Organization commitment of nurses is not only important for nurses but also ill/healthy person and economics. This compilation has been made to evaluate the current status of and the importance of the concept of organizational commitment in the world and in Turkey as well as organizational commitment of nurses.